KEPUASAN KERJA KARYAWAN BERDASARKAN KARAKTERISTIK KERJA, IKLIM KERJA, DAN KOMPENSASI - Agung Nugroho (LPPM UNY, 2001)
Abstract The economics crisis causes the salary accepted by employees is not enough for living. As consequences many demonstration and strike of, they pursuing for the raising salary, raising of presentation premium, food cost, the preparation of a good facility and transportation. From the matter, “Is there influence job characteristic, condition of work and compensation with job satisfaction”. This research has goal to know influence job characteristic, condition of work, and compensation, beside to know difference job satisfaction employees in office section, weaving, and inspecting. The research is doing by survey method, and the result of data analysis mention that: 1) there is a positive influence job characteristic in job satisfaction; 2) there is a positive influence conditions of work in job satisfaction; 3) there is a positive influence compensation in job satisfaction; 4) all at once, there is a positive influence job characteristic, conditions of work, compensation in the job satisfaction. The effective contribution from both the three independent variable to job satisfaction is amount (64%), the rest (36%) contribution by another factors out of this research. The result of differences job satisfaction employees inter section are: 1) office section and weaving section have no differences;2) weaving section and inspecting section have no differences. Keywords: job satisfaction, job characteristics, condition of work, and compensation